Value creation and capture mechanisms in innovation ecosystems: a comparative case study. (1st January 2013) - Ritala, Paavo; Agouridas, Vassilis; Assimakopoulos, Dimitris; Gies, Otto
This study focuses on value creation and capture in innovation ecosystems. It presents and discusses the findings from a qualitative, comparative case study on two European-led innovation ecosystems from the ICT and aerospace and defence sectors. The purpose of the research is to explore the tangible and intangible mechanisms related to how leading firms may facilitate value creation and capture in this context. In particular, we focus on mechanisms related to the building phase to help attract and gather relevant stakeholders, and on the management phase to help maintain and realise the business goals of all ecosystem participants. We also discuss the differences between the case industries concerning the effectiveness and usage of such mechanisms. Overall, the research findings provide new evidence on the facilitating initiatives, underlying mechanisms and structures that are related to the leading firms' orchestration of innovation ecosystems.